2001
DOI: 10.1093/ajcn/73.2.421s
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics—compensation for lactase insufficiency

Abstract: Yogurt and other conventional starter cultures and probiotic bacteria in fermented and unfermented milk products improve lactose digestion and eliminate symptoms of intolerance in lactose maldigesters. These beneficial effects are due to microbial beta-galactosidase in the (fermented) milk product, delayed gastrointestinal transit, positive effects on intestinal functions and colonic microflora, and reduced sensitivity to symptoms. Intact bacterial cell walls, which act as a mechanical protection of lactase du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
217
0
14

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(239 citation statements)
references
References 54 publications
5
217
0
14
Order By: Relevance
“…This is in line with other studies [6,8,9] showing that not all individuals with lactose malabsorption report symptoms from food containing lactose. T he colonic micro biota is variable [28] and the individual sensitivity to feel distension of the colon and to sense discomfort varies [29] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with other studies [6,8,9] showing that not all individuals with lactose malabsorption report symptoms from food containing lactose. T he colonic micro biota is variable [28] and the individual sensitivity to feel distension of the colon and to sense discomfort varies [29] .…”
Section: Discussionsupporting
confidence: 93%
“…celiac disease [3] . Cases of individuals suspecting they have lactose intolerance are more common than the true prevalence of adult-type hypolactasia [4][5][6][7][8][9] . It has been shown that lactose-restricted diets improve symptoms markedly for example in IBS patients with lactose malabsorption and reduce the number of visits to the outpatient clinics [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Related symptoms include bloating, cramping, flatulence and loose stool and some reports also suggest that they lead to irritability bowel syndrome (Joachim 1999;Vesa et al 2000). The rate of LI varies in the population and the rate of incidence of LI in different ethnic races worldwide is provided in Table 1 (Scrimshaw and Murray 1988;de Vrese et al 2001). As seen from the table, highest rates of LI are found in the Asian populations, Native Americans and African Americans (60-100 %), while lowest rates are found in people of northern European origin (including North Americans).…”
Section: Lactose Intolerance (Li)mentioning
confidence: 99%
“…Számítások alapján 50 g laktózból bakteriális fermentá-ció révén 17 liter hidrogén keletkezik: ennek legnagyobb részét felhasználja a többi bélbaktérium [13]. Más szá-mítás szerint in vitro széklet jelenlétében 1 gramm glü-kózból 100 ml H 2 keletkezik [14].…”
Section: A Bakteriális Laktázunclassified